From Punitive Response to Civic Safeguarding: Optimizing a Pentahelix Policy Community Model for Preventing Pedophilia-Related Violence Against Children In Indonesia - Bayu Suseno; Muhammad Mustofa; Puspitasari; Ricardi S. Adnan (Jurnal Kewarganegaraan, 2026)
Pedophilia-related violence against children in Indonesia is still addressed predominantly through punitive law-enforcement responses, while participatory prevention, civic reporting capacity, and cross-sector coordination remain fragmented. This article aims to formulate a policy community model that connects pentahelix collaboration with citizenship education in order to strengthen child safeguarding. The study uses an integrative literature review and policy document analysis, guided by Whittemore and Knafl’s review stages, and reports the results using an adapted PRISMA logic. The synthesis shows that effective prevention requires six interrelated praxis syntaxes: evidence building, pentahelix role allocation, sustainable routines, innovation, evaluation, and citizenship campaigns. The article argues that citizenship education should be repositioned from a classroom-centered subject into a civic-learning infrastructure that develops legal awareness, digital literacy, ethical bystander behaviour, and collective responsibility. The study concludes that civic-oriented policy communities can reduce governance fragmentation and should be empirically tested in local child-protection settings.